The Relationship of Platelet Parameters with Duration of Hospitalization and Fatality in COVID-19 Patients - Özkan Gümüşkaya, Perihan; Karakütük Yüztaş, Nur; Özsoy, Neslihan; Kalyon, Semih; Yıldırım, Emine; Şimşek, Funda; Adas, Mine (Cerrahpaşa Medical Journal, 2022)
Objective: In coronavirus disease 2019 infection, indicators are needed to predict survival and length of hospital stay. Our aim is to determine the relationship between thrombocyte parameters, duration of hospitalization, and mortality. Methods: After the ethics committee approval, patients hospitalized with coronavirus disease 2019 with PCR positivity between March and September 2020 were retrospectively screened. Patients were divided into two groups survivors and non-survivors. Intergroup data was evaluated using Kolmogorov–Smirnov, Student’s t-test, Mann Whitney U, chi-square, and Pearson and Spearman’s rho tests by SPSS version 22. Results: Totally 3914 patients were included in the study, of which 1766 (45%) were female and 2148 (55%) were male. The mean age was 59. The mean hospital stay was 10 days. Five hundred and sixty-four (14%) of our patients died. When the survivors and non-survivors are compared, platelet lymphocyte ratio, platelet distribution width,and platelet large cell ratio were higher in the non-survivors. The death in patients with thrombocytopenia was higher than in the group without thrombocytopenia. Patients with higher platelet large cell ratio (PLCR) and those with lower mean platelet volume were hospitalized for longer. Conclusion: Platelet lymphocyte ratio, platelet distribution width, and platelet large cell ratio are the parameters that can be used to predict coronavirus disease 2019 infection mortality, and platelet lymphocyte ratio and mean platelet volume are the parameters to predict hospitalization durations. Cite this article as: Özkan Gümüşkaya P, Karakütük Yüztaş N, Özsoy N, et al. The relationship of platelet parameters with duration of hospitalization and fatality in COVID-19 patients. Cerrahpaşa Med J. 2022;46(2):151-155.